KARAKTERISTIK ANAK YANG MENJALANI TERAPI ANTIRETROVIRAL DI RSPI PROF. DR SULIANTI SAROSO - Nuraidah; Dessie Wanda (MEDIA ILMU KESEHATAN, 2020)
Background: HIV virus disrupt the immune system and becomes a chronic disease that can be experienced by all ages. Objective: This study aims to determine the characteristics of children with HIV/ AIDS who underwent ARV therapy at RSPI Prof. Dr. Sulianti Saroso Method:. The design of this study was descriptive. The population in this study were all children with HIV undergoing ARV therapy at RSPI Prof. Dr. Sulianti Saroso Jakarta. Sampling with total sampling with a total of 56 children Results: The results showed the majority of children with HIV / AIDS were pre-school age (48.21%) and dominated by boys (53.57%) and living in the North Jakarta (66.07%). Most children adhered to treatment (89.29%) and most did not experience side effects (89.29%). The most common concomitant disease was pulmonary TB (51.79%), the most common nursing problem was nutritional changes (30.36%). the majority of children do not experience growth and development disorders (94.69%) and most of the labor experienced by children is spontaneous labor (51.79%) and the type of examination to diagnose HIV with EIA examination (67.86%) . Conclusion: This research is expected to be useful for conducting nursing care and management of HIV pediatric patients undergoing ARV therapy